Application Engineered Cement Composite Material to Building Fire Resistance at Coastal Area - Danna Darmayadi (International Conference on Coastal and Delta Areas, 2015)
When building from concrete material on fire for long time, can make damage the material. The degree of damage depended of degree of temperature and duration of fire. This research use Engineered cement composite material to compare with concrete material for building fire resistance. This research  assumed to find out the change of Engineered cement composite strength, modulus of rupture and shear strength pre and post burn. Temperature fire was 600 0c at duration 3 hours with two variation mix design  of Engineered Cement composite. The results showed that the ECC was decrease  of compressive strength, MOR, and shear after burn. Variation one  with result  K 400 decrease 19%, 23% and 45,61% for  compressive strength, modulus of rupture and shear strength. Variation two with result K 350  decrease 20%, 27,2% and 60%  for compressive strength, modulus of rupture and shear strength.  Keyword: Concrete; Post-Burn; ECC (Engineered Cement Composite); Experimental